Structural Flexibility of Ca(V)1.2 and Ca(V)2.2 I-II Proximal Linker Fragments in Solution - Almagor, Lior (The Biophysical Society, 2013)
Voltage-dependent calcium channels (Ca(V)) enable the inward flow of calcium currents for a wide range of cells. Ca(V)1 and Ca(V)2 subtype α1 subunits form the conducting pore using four repeated membrane domains connected by intracellular linkers. The domain I-II linker connects to the membrane gate (IS6), forming an α-helix, and is bound to the Ca(V)β subunit. Previous studies indicated that this region may or may not form a continuous helix depending on the Ca(V) subtype, thereby modulating channel activation and inactivation properties. Here, we used small-angle x-ray scattering and ensemble modeling analysis to investigate the solution structure of these linkers, extending from the membrane domain and including the Ca(V)β-binding site, called the proximal linker (PL). The results demonstrate that the Ca(V)1.2 PL is more flexible than the Ca(V)2.2 PL, the flexibility is intrinsic and not dependent on Ca(V)β binding, and the flexibility can be most easily explained by the presence of conserved glycines. Our analysis also provides a robust example of investigating protein domains in which flexibility plays an essential role.